2020
DOI: 10.1186/s12967-020-02395-9
|View full text |Cite
|
Sign up to set email alerts
|

The clinical application of electrical impedance technology in the detection of malignant neoplasms: a systematic review

Abstract: Background Electrical impedance technology has been well established for the last 20 years. Recently research has begun to emerge into its potential uses in the detection and diagnosis of pre-malignant and malignant conditions. The aim of this study was to systematically review the clinical application of electrical impedance technology in the detection of malignant neoplasms. Methods A search of Embase Classic, Embase and Medline databases was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In previous studies, the measurements of the impedance spectra of cervical tissue using a four-electrode probe showed the feasibility of assessing the progress of cervical dysplasia [ 10 , 24 ]. However, the sensitive region of the four-electrode measurement method was limited to a local region due to the size of the electrodes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, the measurements of the impedance spectra of cervical tissue using a four-electrode probe showed the feasibility of assessing the progress of cervical dysplasia [ 10 , 24 ]. However, the sensitive region of the four-electrode measurement method was limited to a local region due to the size of the electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al reported that the electrical impedance spectra on the cervix could separate normal and CIN [ 9 ]. Thus, bioimpedance spectroscopy can potentially facilitate cancer screening [ 10 ], thereby reducing the incidence of cervical cancer among women in developing countries. Subsequently, many studies have evaluated whether CIN can be diagnosed based on the electrical properties of cervical tissues [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioimpedance has been valuable in detecting various cancers, including skin, thyroid, liver, cervix, and breast cancers (5)(6)(7)(8)(9)(10)(11)(12), with breast cancer being the most extensively studied bioimpedance technology (9)(10)(11)(12). It is well known that cancerous tissue has distinctly different electrical properties from non-cancerous tissue (13). This has been attributed to the high water and sodium content within cancerous tissues, altered membrane composition, the nucleus-to-cytoplasm ratio, and cellular composition and density (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The conductivity (σ) and permittivity (ε) of different biological tissues not only vary in terms of frequency, but also change with their physiological and pathological states; therefore, these can be used as indicators for biomedical or clinical applications to detect and diagnose diseases 4 . Although certain frequency ranges of electrical properties have been linked to pathological states of tissues, reports correlating σ and ε with physiological and pathological characteristics of cells are rare 5 . However, for realizing clinical applications of σ and ε, it is critical to understand these correlations.…”
Section: Introductionmentioning
confidence: 99%